Product and Service Quality and Growth of Agriculture Firms in Nigeria. Implication for the Environment Management - EGBERI, Kelvin Agbarha; OBOREH, Justina (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022DO - 10.14505/jemt.v13.3(59).05, 2022)
Acknowledging that improved customers’ satisfaction led to growth, organizations in the agricultural sector are thus aiming for improved products and service quality in order to actualize growth-oriented goal. This paper therefore assessed the impact of product and service quality on the growth of agricultural firms in Nigeria with implication for the environment management. Secondary data of seven (7) agriculture firms were sampled from 2012-2021 and data comprised of revenue growth and market to book-value (proxies for growth) and dummy variable was used as proxy for product and service quality. Multivariate regression results showed that improved product and service quality significantly and positively affect agriculture firms’ growth in Nigeria; the implication of the results is that product and service quality can be used by the environment manager in promoting firms’ growth in Nigeria. Findings call for policy recommendation for the environment managers, government, and researchers alike.